Leveraging Supply Chain Integration for Operational Excellence: The Mediating Role of Product Innovation Capability in Indonesian Apparel SMEs - Muzaky, Mohamad Adnan; Nursyamsiah, Siti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study investigates the effect of supply chain integration, comprising internal, supplier, and customer integration, on operational performance, with product innovation capability as a mediating variable, in Indonesian apparel SMEs. Using a quantitative approach, survey data were collected from 151 respondents selected through purposive sampling and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results reveal that all three dimensions of supply chain integration positively and significantly enhance product innovation capability, which in turn strongly improves operational performance. Furthermore, product innovation capability mediates the relationship between each integration dimension and operational performance, underscoring its role as a strategic link between supply chain coordination and performance outcomes. The findings contribute to the literature by integrating the dynamic capability perspective into the supply chain innovation performance nexus and highlight the need for SMEs to strengthen both integration and innovation capabilities to achieve operational excellence and competitiveness. Practical implications and recommendations for future research are also discussed.